Finite element modelling of the inertia friction welding of a CrMoV alloy steel including the effects of solid-state phase transformations - Bennett, Chris (Elsevier, 2015)
Finite element (FE) process modelling of the inertia friction welding (IFW) between two tubular CrMoV components has been carried out using the DEFORM-2D (v10.2) software. This model has been validated against experimental test welds of the material; this included process data such as upset and rotational velocity as well as thermal data collected during the process using embedded thermocouples. The as-welded residual stress from the FE model has been compared to experimental measurements taken on the welded component using the hole drilling technique. The effects of the solid-state phase transformations which occur in the steel are considered and the trends in the residual stress measurements were well replicated when compared to the experimental data.